Pomadasys empherus, a new species of haemulid fish from the tropical eastern Pacific - Bussing, William A (Revista de Biología Tropical, 1993)
A fifth eastem Pacific species of Pomadasys is described from four specimens collected from two localities on the west coast of Costa Rica. The species is similar to P. branickii in a number of respects, but in general appearance most resembles P. macracanthus. It is distinguished by the coarse serrations on the preopercular margino deep body, long first anal fin spine and numerous other characteristics in which it differs from other Pornadasys species.